STATUS HUKUM KEUANGAN PERSEROAN TERBATAS (PERSERO) BERDASARKAN TEORI BADAN HUKUM DAN TEORI TRANSFORMASI KEUANGAN - Debby, Debby (Justitia et Pax, 2021)
The lack of understanding about public finance and private finance will affect the procedures for the management and accountability of a finance. Based on Article 2 letter g Law Number 17 of 2003, separated state assets which are used as capital participation (in this case money) in Limited Liability Companies (Persero) are part of state finance. This is not in line with the theory of legal entities and the theory of financial transformation. Based on that, this paper aims to explain the financial legal status of Limited Liability Companies (Persero) based on the theory of legal entities and the theory of financial transformation. This research is in the form of juridical-normative. The data used is secondary data consisting of primary and secondary legal materials. Data analysis was carried out using qualitative methods and the form of the results of this study was prescriptive analysis. Based on the theory of legal entities, a Limited Liability Company (Persero) is a private legal entity that has private power that can take provate legal actions and is subject to the provisions of private law. Based on the theory of financial transformation, the legal status of finance changes (transform) as a result of the legal action of transferring and separating finances from one legal subject to another. The transformation of the financial legal status causes changes in rights and obligations in the control and ownership of money in a legal entity so that management, responsibility and risk are under the new legal subjects.